Analytical and Numerical Investigation of Knee Brace Equipped with a Shape Memory Alloy Damper. (13th September 2022) - Shakiba, Milad; Mortazavi, Seyed Mohammad Reza
Abstract : Shape memory alloys (SMAs) are some of the new materials that have attracted the attention of many engineers due to their unique behavior. The most important advantage of these materials is their superelastic behavior, which allows the alloy to return to its original shape after a large deformation. In superelastic behavior, the shape memory alloy can also dissipate a significant amount of energy while returning to its original shape. In this research, the superelastic alloy made of nitinol has been used to improve the performance of knee dampers. For this purpose, a frame equipped with a knee damper was selected as the reference model and was modelled in Abaqus numerical software and validated with an experimental model. After ensuring the correct behavior of the numerical model, the SMA damper was installed perpendicular to the knee damper, between the knee damper and the beam to column connection. In this paper, two parameters of the SMA damper cross section area and SMA length were investigated. Based on the observed results, increasing the length of SMA increases the system resistance. As the cross section area of the SMA damper increases, the effect of the SMA length on the resistance of the system increases. On the other hand, increasing the cross section area of the SMA significantly increases the recentering of the system. Due to the significant recentering that the SMA damper creates in the structure, the amount of energy dissipation of the system is reduced compared to the reference model. The amount of dissipated energy depends on the length and cross section area of the SMA damper. Thus, the longer the SMA, the greater the energy dissipation, and the lower the SMA cross section area, the lower the system energy dissipation.